(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The dye sensitized solar cells have been assembled by using natural dye extracted from Terminalia catappa fruits. The photoelectrode for dye sensitized solar cell were prepared using green synthesized ZnO nanoparticles using doctor blade technique. The photoelectrode were sensitized using the extracted dyes. The fabricated solar cell exhibited short circuit current density of 4.9 mA and open circuit voltage of 0.472 V. The efficiency of the cell was found to be 1.58%. The photovoltaic performance of the constructed solar cell show good conversion efficiency. This indicates that Terminalia catappa fruit extracts can be used as an effective sensitizer.